Interrelations Between School-Based Services, Dietary Intake and Micronutrient Deficiencies Among School-Going Children and Adolescents Aged 5–19 Years in India. (29th May 2020) - Chopra, Mansi; Lahiri, Anwesha; Rastogi, Priyanshu; Bhanot, Arti; Bakshi, Anjani; Mathur, Pulkit; Ramaswamy, Gomathi; Yadav, Kapil; Sethi, Vani; Scott, Samuel; Menon, Purnima; Nguyen, Phuong
Abstract: Objectives: India is home to 119 million children (CH; 5–9 y) and 253 million adolescents (AD; 10–19 y), a majority of whom suffer from multiple micronutrient deficiencies (MND). Given high school enrolment levels in India (90% of CH and 75% of AD) schools are a good platform for services and behavior change interventions targeted toward this age group. We sought to analyze the prevalence and predictors of MND in school going CH and AD in India. Methods: Data from India's Comprehensive National Nutrition Survey 2016–18 were analyzed separately for CH aged 5–9 y (n = 10, 640), AD aged 10–14 y (n = 5390) and AD aged 15–19 y (n = 3693). Serum/plasma concentrations of ferritin, retinol, B12, erythrocyte folate, 25-hydroxyvitamin D, zinc and C-reactive protein were measured. We assessed the weighted prevalence of each MND using established WHO cutoffs, after adjusting ferritin and retinol for inflammation. Primary predictors of MND were dietary intake and access to school services. Multivariable logistic regression models were used to examine associations between these factors and each MND, controlling for socio-demography (sex, residence, wealth quintile, ethnicity, parental education, siblings) and hygiene-sanitation services. Results: The top three micronutrient deficiencies were folate (29%), vitamin A (22%), vitamin D (19%) among CH and folate (38%), zinc and B12 (31% each) in AD. One or more MND affected 69% of CH and 83% of AD. In CH, deworming was associated with reduced odds of folate deficiency (AOR and 95% CI: 0.80, 0.68–0.94) and health camps were associated with vitamin A deficiency (0.68, 0.51–0.91). In AD 10–14y, receipt of free school meals had lower odds of B12 deficiency (0.66, 0.49–0.88). In AD 15–19y, health camps were inversely associated with vitamin D deficiency (0.69, 0.51–0.95). CH and AD who consumed green leafy vegetables, pulses and fruits daily had reduced odds of iron, folate or vitamin D deficiencies (AORs: 0.58–0.81). Consumption of fish, chicken or meat (≥2 times/week) was associated with lower odds of almost all MND in CH (AORs: 0.39–0.75), and of iron and B12 deficiencies in AD (AORs: 0.42–0.66). Conclusions: Most CH and AD in India suffer from multiple MND. Improving diet quality through school meals and strengthening school-based health services may contribute to MND reductions in this population. Funding Sources: UNICEF, POSHAN.